2017
DOI: 10.1186/s12891-017-1690-2
|View full text |Cite
|
Sign up to set email alerts
|

Patellar tendinopathy in young elite soccer– clinical and sonographical analysis of a German elite soccer academy

Abstract: BackgroundThe prevalence of patellar tendinopathy is elevated in elite soccer compared to less explosive sports. While the burden of training hours and load is comparably high in youth elite players (age < 23 years), little is known about the prevalence of patellar tendinopathy at this age. There is only little data available on the influence of age, the amount of training, the position on the field, as well as muscular strength, range of motion, or sonographical findings in this age group. The purpose of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 25 publications
0
19
0
1
Order By: Relevance
“…39 40 In elite volleyball players aged 15-19 years, the rate of jumper's knee was as high as 11%. 41 An ultrasound study of 119 young soccer players (mean age 15.97 years) showed high rates of structural abnormalities within the tendon, 42 and other studies demonstrated a high correlation between a clinical tendinopathy and structural intratendinous alterations in ultrasound. 43 44 In the current study with a cohort of youth skiers, even a higher proportion of the athletes had clinical complaints at the distal or proximal patellar tendon (overall: 31.5%; distal: 17.6%; proximal: 18.5%).…”
Section: Discussionmentioning
confidence: 99%
“…39 40 In elite volleyball players aged 15-19 years, the rate of jumper's knee was as high as 11%. 41 An ultrasound study of 119 young soccer players (mean age 15.97 years) showed high rates of structural abnormalities within the tendon, 42 and other studies demonstrated a high correlation between a clinical tendinopathy and structural intratendinous alterations in ultrasound. 43 44 In the current study with a cohort of youth skiers, even a higher proportion of the athletes had clinical complaints at the distal or proximal patellar tendon (overall: 31.5%; distal: 17.6%; proximal: 18.5%).…”
Section: Discussionmentioning
confidence: 99%
“…A color Doppler examination to determine intratendinous blood flow was performed with the participants laying supine with the dominant knee flexed to 30° (0° = full extension). The joint angle was chosen based on former recommendations (Giombini et al, 2013; Bode et al, 2017) to reduce slack but avoid any passive forces that might induce vascular compression. The ultrasound system, probe model and orientation were as described above, yet the system settings were set as follows: CFM mode, 13 MHz frequency, 750 Hz peak repetition frequency, 1.1 by 1.6 cm color box size (spanning from the deep insertion at the patella or tibial tuberosity to the central portion of the tendon, respectively).…”
Section: Methodsmentioning
confidence: 99%
“…The knee joint pain aggravates with activity and alleviates after rest. With the patients condition worsened, the pain will be persistent and aggravated when squatting or going up and downstairs [32, 33].…”
Section: Clinical Manifestation (Includes Symptom Sign Laboratormentioning
confidence: 99%